Blockade of LAG-3 Immune Checkpoint Combined With Therapeutic Vaccination Restore the Function of Tissue-Resident Anti-viral CD8+ T Cells and Protect Against Recurrent Ocular Herpes Simplex Infection and Disease - Roy, Soumyabrata; Coulon, Pierre-Grégoire; Srivastava, Ruchi; Vahed, Hawa; Kim, Grace J.; Walia, Sager S.; Yamada, Taikun; Fouladi, Mona A.; Ly, Vincent T.; BenMohamed, Lbachir (Frontiers in Immunology, 2018)
Recurrent viral diseases often occur after the viruses evade the hosts’ immune system, by inducing exhaustion of antiviral T cells. In the present study, we found that functionally exhausted herpes simplex virus type 1 (HSV-1) -specific CD8+ T cells, with elevated expression of lymphocyte activation gene-3 (LAG-3), an immune checkpoint receptor that promotes T cell exhaustion, were frequent in symptomatic (SYMP) patients with a history of numerous episodes of recurrent corneal herpetic disease. Similarly, following UV-B induced virus reactivation from latency the symptomatic wild-type (WT) B6 mice that developed increase virus shedding and severe recurrent corneal herpetic disease had more exhausted HSV-specific LAG-3+CD8+ T cells in both trigeminal ganglia (TG) and cornea. Moreover, a therapeutic blockade of LAG-3 immune checkpoint with antagonist antibodies combined with a therapeutic immunization with gB498-505 peptide immunodominant epitope of latently infected B6 mice significantly restored the quality and quantity of HSV-1 gB498-505 specific CD8+ T cells in both TG and cornea and protected against UV-B induced recurrent corneal herpes infection and disease. In contrast to dysfunctional HSV-specific CD8+ T cells from WT B6 mice, more functional HSV-specific CD8+ T cells were detected in LAG-3-/- deficient mice and were associated with less UV-B induced recurrent corneal herpetic disease. Thus, the LAG-3 pathway plays a fundamental role in ocular herpes T cell immunopathology and provides an important immune checkpoint target that can synergizes with T cell-based therapeutic vaccines against symptomatic recurrent ocular herpes.